2013
DOI: 10.1063/1.4853435
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a multiple-coincidence ion-momentum imaging spectrometer

Abstract: The design and performance of a high-resolution momentum-imaging spectrometer for ions which is optimized for experiments using synchrotron radiation is presented. High collection efficiency is achieved by a focusing electrostatic lens; a long drift tube improves mass resolution and a position-sensitive detector enables measurement of the transverse momentum of ions. The optimisation of the lens for particle momentum measurement at the highest resolution is described. We discuss the overall performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Momentum-resolved, multiple-ion-coincidence measurements with high-resolution synchrotron radiation can directly correlate the F and Xe fragment ions and their energies. 82,83 A recent experiment on core-hole decays of CS 2 using coincidence spectroscopy revealed two charge redistribution and ion fragmentation mechanisms in which the S 1s core hole can be considered to be either localized or delocalized on one or two of the S sites. 84 It would be interesting to investigate such effects for the case of the F 1s-LUMO resonance of XeF 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Momentum-resolved, multiple-ion-coincidence measurements with high-resolution synchrotron radiation can directly correlate the F and Xe fragment ions and their energies. 82,83 A recent experiment on core-hole decays of CS 2 using coincidence spectroscopy revealed two charge redistribution and ion fragmentation mechanisms in which the S 1s core hole can be considered to be either localized or delocalized on one or two of the S sites. 84 It would be interesting to investigate such effects for the case of the F 1s-LUMO resonance of XeF 2 .…”
Section: Discussionmentioning
confidence: 99%
“…27 The lens potential used in this study ensures that all ions up to a kinetic energy of about 19 eV are collected; this has been verified in separate studies. 28 The measurements were performed at the soft x ray undulator beamline I411 at MAX-lab in Lund, Sweden. 29 The contribution from secondorder light for the photon energies in this study is negligible.…”
Section: Methodsmentioning
confidence: 99%
“…According to them, the timeof-flight difference (∆TOF = T 0L (R) − T 0L (0)) is proportional to the square root of mass ( √ m) of the particle, where T 0L (R) is same as described before and T 0L (0) is the time-of-flight of particles with p x = 0, p y = 0 and p z = 0. Unlike, Bomme et al, Laksman and his co-workers 31 have suggested that instead of √ m it should be  m/q. However, in their case, the major contribution to the ∆TOF comes from the field inhomogeneity near the detector and drift tube interface.…”
Section: Simulation Resultsmentioning
confidence: 92%
“…All these spectrometers described above are single field WileyMcLaren type spectrometers. There is only one recent work by Laksman et al, 31 in which the authors have combined both time and space focusing together in a two-field type of spectrometer. In this article, we present detailed features of a three dimensional velocity imaging spectrometer and discuss how this spectrometer can be used for a wide range of recoil ion energy to study fragmentation of atoms and molecules.…”
Section: Introductionmentioning
confidence: 98%